Selective Maslahah: Judicial Reasoning on Child Marriage Dispensation at the Religious Courts of Madura, Indonesia - Moh. Afif Wahyudi; Idzam Fautanu; Siah Khosyi'ah; Ateng Ruhendi (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Although Indonesia raised the minimum legal age for marriage to nineteen years through Law Number 16 of 2019, judicial dispensation remains available, placing Religious Courts at the center of decisions concerning child marriage. This study examines how judges at the four Religious Courts of Madura operationalize maslahah mursalah in marriage dispensation proceedings and evaluates the extent to which their reasoning reflects the objectives of maqasid al-shari'ah. An empirical-juridical qualitative approach was employed using semi-structured interviews with four senior judicial officers, documentary analysis of ten marriage dispensation decisions, and examination of annual court reports from 2020 to 2023. Data were analyzed through qualitative content analysis, thematic coding, and critical legal interpretation, with triangulation applied to strengthen the credibility of the findings. The results reveal that judges consistently invoke maslahah mursalah when justifying marriage dispensation; however, judicial reasoning predominantly emphasizes the protection of religion (hifz al-din) and lineage (hifz al-nasl), while the protection of life, intellect, and property receives limited evidentiary consideration. Pregnancy outside marriage emerges as the principal factor shaping judicial decisions, whereas multidisciplinary assessment and long-term evaluation of children's welfare remain inconsistently implemented. The study concludes that selective application of maslahah is primarily influenced by institutional and evidentiary constraints rather than inadequate doctrinal understanding. These findings contribute to Islamic family law scholarship by proposing a more systematic framework for evaluating judicial reasoning and offer practical recommendations for strengthening child-centered marriage dispensation procedures in Indonesia.